Footshock‐induced plasticity of GABAB signalling in the lateral habenula requires dopamine and glucocorticoid receptors. Issue 6 (1st December 2016) - Lecca, Salvatore; Trusel, Massimo; Mameli, Manuel
Abstract: The activity of lateral habenula (LHb) represents a substrate for the encoding of negative‐valenced events. The exposure to aversive stimuli in naïve mice is sufficient to trigger a reduction in GABAB ‐mediated signaling in the LHb. This is ultimately instrumental for the hyperactivity of LHb neurons and for the establishment of depressive‐like phenotypes. However, the mechanisms responsible for the induction of this aversion‐driven plasticity are missing. Using ex‐vivo patch‐clamp recordings in slices, here we show that exposing mice to a series of inescapable footshocks (FsE) rapidly reduces baclofen‐mediated GABAB currents in the LHb. This plasticity of GABAB signaling requires the activation of the dopamine and stress pathways. Indeed, the systemic administration of dopamine and glucocorticoids receptor antagonists prevents the FsE‐induced reduction of GABAB currents in the LHb. To test whether the recruitment of these receptors occurs within the LHb, we exposed slices from control mice to either dopamine or corticosterone. Both manipulations failed to alter the amplitudes of baclofen‐mediated GABAB currents. Altogether, these data suggest that dopamine and stress signaling are necessary for the induction of FsE‐evoked GABAB plasticity in the LHb. However, the activation of these specific receptors may occur in structures different than the LHb, suggesting a circuit‐based mechanism for this form of plasticity. These findings provide mechanistic insights on aversion‐driven plasticity within the LHb. Abstract : Stressful events including foot‐shocks produce a reduction in GABA‐B receptor function within the lateral habenula. While this effect requires both dopamine and glucocorticoid receptors, their localization is outside the lateral habenula. Altogether, these findings describe molecular mechanisms underlying aversion‐driven cellular plasticity in mice.